Synthesis, Characterization And Biological Activity Of Organotin Compounds Derived From Organic Acids - Yip, Foo Win (2009)
The complexes were synthesized by the condensation reaction between dialkyltin(IV) oxide, R2SnO (R= methyl and butyl), bis[tributyltin(IV)] oxide, (Bu3Sn)2O or triphenyltin(IV) hydroxide, Ph3SnOH with the selected organic acids. Kompleks disintesiskan menerusi tindak balas kondensasi dialkilstanum(IV) oksida, R2SnO (R= metil dan butil), bis[tributilstanum(IV)] oksida, (Bu3Sn)2O atau trifenilstanum(IV) hidroksida, Ph3SnOH dengan asid organik yang tertentu.